2016
DOI: 10.1088/1009-0630/18/11/07
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown Electric Field of Hot 30% CF3I/CO2Mixtures at Temperature of 300–3500 K During Arc Extinction Process

Abstract: We calculated the uniform dielectric breakdown field strength of residual 30% CF3I/CO2 gas mixtures during the arc extinction process over the temperature range 300-3500 K at 0.1 MPa. The limiting reduced field strengths are decided by a balance of electron generation and loss based on chemical reactions estimated by the electron energy distribution function (EEDF), which employs the Boltzmann equation method with two-term expanding approximation in the steady-state Townsend (SST) condition. During the insulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Alternative arc‐extinguishing gases for gas circuit breakers are roughly categorized into two types, natural gases such as CO 2 , N 2 , O 2 , and so on, and artificial gases such as C 5 F 10 O, CF 3 I, C 4 F 7 N, and so on. As specifically proposed examples, CO 2 and its combinations, such as CO 2 /O 2 , CO 2 /C 5 F 10 O, CO 2 /CF 3 I, CO 2 /O 2 /C 4 F 7 N, and CO 2 /O 2 /C 5 F 10 O, have been researched [2–16]. Here, the artificial gases should be mixed with natural gases, and not be used alone, because of their high liquefying temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative arc‐extinguishing gases for gas circuit breakers are roughly categorized into two types, natural gases such as CO 2 , N 2 , O 2 , and so on, and artificial gases such as C 5 F 10 O, CF 3 I, C 4 F 7 N, and so on. As specifically proposed examples, CO 2 and its combinations, such as CO 2 /O 2 , CO 2 /C 5 F 10 O, CO 2 /CF 3 I, CO 2 /O 2 /C 4 F 7 N, and CO 2 /O 2 /C 5 F 10 O, have been researched [2–16]. Here, the artificial gases should be mixed with natural gases, and not be used alone, because of their high liquefying temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The partial discharge inception voltage of CF 3 I/CO 2 was measured in needle-plate electrodes and the result indicated that CF 3 I/CO 2 with the mixing ratio of 20%-30% was able to replace SF 6 as an insulation medium [17]. The dielectric breakdown field strength of CF 3 I/CO 2 during the arc extinction process was calculated and the result showed that the insulation recovery ability of CF 3 I/CO 2 was adverse to arc quenching [18]. The V-t characteristics of the CF 3 I/N 2 and CF 3 I/air mixtures were measured by using steep-front voltage, and the CF 3 I/N 2 or CF 3 I/air mixtures containing 60% CF 3 I possessed comparable V-t characteristics to SF 6 [19].…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 gas is a significant medium either as a puffer gas mixed with other gases or a potential substitute of SF 6 in switchgear equipment. Although a lot of work related to the CO 2 plasma modelling have been published recently [11][12][13][14], there is few literatures that could give satisfactory arc model for CO 2 in switching application.…”
Section: Introductionmentioning
confidence: 99%